2018
DOI: 10.11607/ofph.1924
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Posterior Disc Displacement of the Temporomandibular Joint in Patients with Temporomandibular Disorders: Systematic Review and Meta-Analyses

Abstract: This meta-analysis showed a very low prevalence rate of PDD in TMD patients. The limited literature did not allow conclusions to be drawn about the PDD-related features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Anterior disc displacement is the most frequent form of disc displacement, while posterior dislocation is the least prevalent [10]. In our study, posterior dislocation was observed in only 2.5% of patients [1 patient], which is consistent with the findings of Afroz et al's [19] meta-analysis study. The study reported an overall prevalence of posterior disc displacement [PDD] of 0.7% for the number of joints affected and 0.9% for the number of patients affected.…”
Section: Resultssupporting
confidence: 92%
“…Anterior disc displacement is the most frequent form of disc displacement, while posterior dislocation is the least prevalent [10]. In our study, posterior dislocation was observed in only 2.5% of patients [1 patient], which is consistent with the findings of Afroz et al's [19] meta-analysis study. The study reported an overall prevalence of posterior disc displacement [PDD] of 0.7% for the number of joints affected and 0.9% for the number of patients affected.…”
Section: Resultssupporting
confidence: 92%
“…The frustration expressed over the persistence of symptoms like the clicking sound, despite treatment efforts, aligns with findings in the literature. For example, Afroz et al (2018), in a systematic review, noted that the multifactorial etiology of TMD makes it challenging to achieve consistent treatment outcomes [33]. This complexity often results in a trial-and-error approach, which can be disheartening for both practitioners and patients.…”
Section: Clinical Efficacy and Practitioner Challengesmentioning
confidence: 99%
“…There is another type of disc displacement called posterior disc displacement (PDD). Although PDD is reported to be very rare [ 10 ], symptoms such as pain, clicking, and locking can still occur [ 11 ].…”
Section: Introductionmentioning
confidence: 99%